2017
DOI: 10.1177/1060028017717282
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Analysis of Factors Associated With Apixaban-Related Bleeding in Hospitalized Patients With End-Stage Renal Disease on Hemodialysis

Abstract: The association between these factors and increased bleeding should prompt concern for long-term anticoagulation with apixaban in patients with ESRD receiving chronic HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…In contrast to the above, a recent retrospective analysis of factors associated with apixaban related bleeding events in ESRD patients on hemodialysis, describe increased risk of bleeding with increased exposure to apixaban . This retrospective analysis did not include a warfarin comparator group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the above, a recent retrospective analysis of factors associated with apixaban related bleeding events in ESRD patients on hemodialysis, describe increased risk of bleeding with increased exposure to apixaban . This retrospective analysis did not include a warfarin comparator group.…”
Section: Discussionmentioning
confidence: 99%
“…found no statistically significant difference in the major or overall bleeding event rate of patients taking apixaban vs warfarin, including the subgroup of patients on dialysis . In addition, continuation of apixaban after inpatient admission, the daily dose of apixaban, and the number of hemodialysis sessions have been associated with an increased risk of bleeding …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its high degree of protein binding, dialysis clearance is low (18 ml/min), resulting in a 14% decrease in drug exposure (49). In a recent retrospective analysis of patients on hemodialysis, cumulative days of apixaban use in an outpatient setting, higher total daily apixaban doses, and total hemodialysis sessions were independent risk factors for bleeding events (adjusted odds ratio, 13.07; 95% CI, 1.54 to 110.54; adjusted odds ratio, 1.72; 95% CI, 1.20 to 2.48; and adjusted odds ratio, 2.04; 95% CI, 1.06 to 3.92, respectively) (50). Another PK/PD study prescribed a single 10-mg dose to 24 patients with CKD and various categories of creatinine clearance and eight healthy controls (51).…”
Section: Pharmacology In Kidney Diseasementioning
confidence: 99%
“…58 Other retrospective studies confirmed these findings. Two subsequent meta-analyses, 59,60 which included smaller observational studies, [61][62][63][64] found that apixaban was associated with less major bleeding in HD patients with NVAF than warfarin with similar efficacy in prevention of stroke and systemic embolism. A recent systematic review concluded that in HD patients, compared to warfarin there was an increased risk of major bleeding with rivaroxaban (RR, 1.45; 95% CI, 1.09-1.93) and dabigatran (RR, 1.76; 95% CI, 1.44-2.15), while there was no difference between apixaban and warfarin.…”
Section: Safe T Y Con Cern S With Warfarin V Er Sus N Oac Smentioning
confidence: 99%